Graceland. The complete season 3 [videorecording (DVD)] - Eastin, Jeff; Ehrlich, Jon (20th Century Fox Home Entertainment, 2016)
In the gripping third season of Graceland, the team is shaken after a deadly attack on one of their own. As Mike Warren recovers, the other members of this beach house full of feds find it difficult to regain normalcy, and increasingly find themselves facing new dangers. Paul, Charlie, Johnny, Dale and Paige embark on their respective next dangerous undercover mission, with bad guys to pursue and even more secrets to be kept under wraps. The FBI, DEA and ICE housemates must rebound, reunite and rebuild their lives in their sanctuary by the sea.